Perceptions of rural communities on climate change and its economic impacts on the livelihood : a case of Motupa Community in Tzaneen, Limpopo Provine - Makwala, Nkomi Shaun (My University, 2020)
Climate is a primary component of agricultural productivity, and as such, it influences the vulnerability of the households, communities and the broader economy. A heavy dependence on climate-sensitive economic sectors, in particular agriculture, makes South Africa particularly vulnerable to climate change. The study aims to explore the perceptions of the Motupa community members on climate change and its economic impact on their livelihood patterns. Motupa community is a rural area situated on the Southern part of Tzaneen, Limpopo province South Africa. A triangulation of focus group discussion and semi-structured data collection method were adopted. Analysis was based on 20 participants who were purposively selected at Motupa community aged between 45 to 90 years to obtain their perceptions of climate change and its economic impact on livelihood. The study found that climate change in rural communities has a major impact during the past years. Climate change has contributed to major rural environmental stresses affecting local resources such as water, subsistence agriculture, economic activities, farming, livestock, forest and soil, among other natural assets. The rural livelihoods show high levels of vulnerability to rapid climate change due to notable low adaptive capacity. The high level of vulnerability to changing climate is exposing the study population to increased prevalence of poor production, crop and livestock failure, food insecurity, poverty, malnutrition, diseases and viruses, among other impacts. The increase in temperatures and unpredictable rainfall patterns are major causes of climate change that Motupa community members have identified. Low production affects most community economic activities, resulting in livelihood vulnerability. The study concludes that factors creating barriers to climate change adaptation are related to those contributing to poverty and holding back sustainable local development. The study indicates that community members are using their indigenous knowledge as adaption to cope with the current climate change.
Thesis (M.A. (Sociology)) -- University of Limpopo, 2020
Keywords: Agricultural productivity; Rural communities; Climate; Economy; Climatic changes; Subsistence economy